1993
DOI: 10.2343/geochemj.27.201
|View full text |Cite
|
Sign up to set email alerts
|

Noble gas signatures of magmatic sources and processes.

Abstract: The degree of partial melting affects the concentration of noble gases in a lava. However, this effect is apparent only for heavier noble gases (Ar, Kr, Xe), in the case of Loihi samples, because kinetic proc esses work more effectively for lighter noble gases (He, Ne). Further, the amounts of atmospheric Ar ob served in volcanic rocks are sometimes lower than those expected from the solubility data for Ar in the atmosphere at the surface. This suggests that the samples did not equilibrate with the atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Searches in the Earth's crustal rocks also failed to find "missing" Xe. Kaneoka [1993] has shown that mantlederived rocks have higher Xe/Kr ratios than the atmosphere, implying that Earth's Xe may be trapped within the mantle. This could not account, however, for Xe that was brought in during the heavy bombardment period because that Xe would have been impact degassed directly into the atmosphere.…”
Section: Copyright 1999 By the American Geophysical Unionmentioning
confidence: 99%
“…Searches in the Earth's crustal rocks also failed to find "missing" Xe. Kaneoka [1993] has shown that mantlederived rocks have higher Xe/Kr ratios than the atmosphere, implying that Earth's Xe may be trapped within the mantle. This could not account, however, for Xe that was brought in during the heavy bombardment period because that Xe would have been impact degassed directly into the atmosphere.…”
Section: Copyright 1999 By the American Geophysical Unionmentioning
confidence: 99%
“…However, they have not been often used as tracers of mag matic processes and volcanic systems. Since it is expected that noble gas isotopes would be sensi tively affected by magmatic events, such as magma mixing and assimilation, they might have a po tential to contribute to volcanology (Hilton et al, 1993;Kaneoka, 1993;Marty et al, 1994). In this study, we have applied noble gas signatures to the magma of Unzen Volcano, Japan (Fig.…”
Section: Introductionmentioning
confidence: 99%